Network analysis of the relationships between voice behavior and team psychological safety climate among Chinese nurses - Miaoji Lu; Ruinan Xia; Rui Wang; Xiaofang Zou (BMC Nursing)
Abstract Background Nurse voice behavior is a critical factor in ensuring patient safety. Although there is a correlation between voice behavior and psychological safety within nurse teams, the intricate relationship between them has not been sufficiently explored in the literature. Design A multi-center cross-sectional study was conducted. Methods From April to June 2022, clinical nurses were recruited from five cities in Guangdong Province, China using convenience sampling. Data were collected using validated scales, including the Voice Behavior Scale and Team Psychological Safety Climate Scale. Network analysis was employed to visualize the interactive relationships among variables. Statistical analysis was performed using SPSS 26.0 for baseline characteristics description. Network analysis was conducted on the RStudio platform, with network visualization implemented using the “qgraph” package, network centrality metrics calculated via the “qgraph” and “networktools” package, and network accuracy estimation along with stability testing performed using the “bootnet” package. Results This study included a total of 812 nurses, with a mean age of 33.94 ± 7.95 years, of whom 96.6% were female. The mean scores for the voice behavior scale and the team psychological safety scale were 37.04 ± 5.88 and 58.01 ± 7.57, respectively. Network analysis revealed that the edges between nurses’ voice behavior and team psychological safety were primarily positively correlated. Thestrongest influence was observed for “team members respect the suggestions and perspectives of others”, which had the highest expected influence coefficient. Bridging connections included " if there is a problem with the work of the unit, dare to put forward opinions and suggestions “, " express your opinion on phenomena that affect work efficiency in the unit, without fear of embarrassment “, " timely dissuade other employees in the unit from bad behavior that affects work efficiency “, " most team members are receptive to new ideas or ways of thinking “, and " collaborate with team members to develop skills and expertise “. These findings highlighted critical pathways linking voice behavior and psychological safety in nursing teams. Conclusion The study revealed moderate levels of voice behavior and team psychological safety among Chinese nurses. Utilizing network analysis, we elucidated the intricate dynamics between these two constructs, identifying six pivotal influencing factors: (1) team members respect the suggestions and perspectives of others, (2) if there is a problem with the work of the unit, dare to put forward opinions and suggestions, (3) express your opinion on phenomena that affect work efficiency in the unit, without fear of embarrassment, (4) timely dissuade other employees in the unit from bad behavior that affects work efficiency, (5) most team members are receptive to new ideas or ways of thinking, and (6) collaborate with team members to develop skills and expertise. These findings underscore the potential for targeted interventions aimed at strengthening these key dimensions to enhance psychological safety and promote voice behavior within nursing teams, ultimately improving team dynamics and organizational outcomes. Trial registration Not suitable.